(untitled) (Al-Qamar, 2020)
The bulk of writings by Western scholars tend to present a negative and distorted picture of various aspects of Islamic civilization. By offering twisted interpretations of historical facts, these writing draw such a hateful image of Islamic history that engenders skepticism and a tendency of self-abnegation among their gullible modern Muslim readers. Muslim scholars have made valuable efforts that aim at correcting the misconceptions spread through this kind of literature. They represent a variety of of perspectives and argumentative approaches to refute the prejudiced viewpoints of Western writers. The present article seeks to briefly explore as to what extent the efforts of Muslim scholars have been successful in exposing the shallowness of Western narratives and bringing to light the fallacies inherent in their style of reasoning and argumentation.